PENGARUH GAYA KOMUNIKASI PRESENTER TALKSHOW “RUMPI NO SECRET” DI TRANS TV TERHADAP AUDIENCE SATISFACTION - Kurniawan Prasetyo (Jurnal Visi Komunikasi, 2019)
Television stations every day present various types of programs whose types are very diverse. One of them is a talk show program. One of the talk show programs. the mainstay of Trans TV is "Rumpi No Secret" which is packaged in a conversation. The talk show "Rumpi No Secret" was hosted by Feni Rose who has a very unique appeal that is able to attract the attention of loyal viewers. The purpose of this research is to find out whether there is an influence from the style of presenter Feni Rose when guiding the talk show "Rumpi No Secret" that aired on Trans Tv to the satisfaction of watching housewives in Kampung Baru RW residents. 10 Kembangan Utara, West Jakarta. This study uses survey research methods in which this method is a study that takes the main sample from a population of data using a questionnaire statement or questionnaire as a primary data collection tool. Data were analyzed by a causal explanative method with a quantitative approach. The theoretical basis used is the uses and gratification theory owned by Blumer and Katz.